The genesis of Georges Florovsky’s philosophical reflection (based on reviews of «Odessa period») - Holubytska, Hanna (Sententiae, 2011)
The author reveals the origins of Georges Florovsky’s philosophical reflexion. The central idea of it is the problem of defining the place and importance of «Odessa period» in his creative heritage. The author pays special attention to Florovsky’s early works.